2017
DOI: 10.1371/journal.pone.0173791
|View full text |Cite
|
Sign up to set email alerts
|

First year physical activity findings from turn up the HEAT (Healthy Eating and Activity Time) in summer day camps

Abstract: BackgroundSummer day camps (SDCs) serve 14 million children yearly in the U.S. and aim to provide participating children with 60 minutes of moderate-to-vigorous physical activity (MVPA). This study evaluated an intervention designed to increase the percent of children meeting this MVPA guideline.DesignTwo-group, pre-post quasi-experimental.Setting/ParticipantsTwenty SDCs serving 1,830 children aged 5–12 years were assigned to MVPA intervention (n = 10) or healthy eating attention control (n = 10).InterventionT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…Child participation in organised sports during term time has been shown to be associated with higher levels of MVPA [35]. Additionally, existing intervention studies have shown that holiday clubs do have the potential to increase PA [17,36]. However, this effect is not consistent and may only be applicable to boys [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Child participation in organised sports during term time has been shown to be associated with higher levels of MVPA [35]. Additionally, existing intervention studies have shown that holiday clubs do have the potential to increase PA [17,36]. However, this effect is not consistent and may only be applicable to boys [17].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, existing intervention studies have shown that holiday clubs do have the potential to increase PA [17,36]. However, this effect is not consistent and may only be applicable to boys [17]. More work is needed to ensure consistency in the quality of holiday club provision with a particular focus on engaging less active children (e.g., girls).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other interventions show promise in promoting health behaviors in the camp setting. A large intervention to expand, extend, and enhance opportunities for PA in summer day camps increased the percentage of children attaining 60 min of physical activity each day at camp by more than 10% [62]. The Healthy Lifestyle Fitness Camp, a free summer day camp in Fresno, CA, for overweight and obese youth, provided 3 h of daily moderate physical activity, healthy snacks, and nutrition education [63].…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of 46 participants showed increases in overall daily PA and MVPA and substantial decreases in sedentary time, though favorable changes in BMI z-score were not observed [64]. Providing camp staff with competency-based professional development, designed to foster skill building as opposed to rote knowledge, can also support healthy eating and physical activity in summer day camps [62, 65]. Recent studies show that there is room for improvement in the nutritional quality of foods served in camp and brought by campers [66, 67], so efforts to improve the camp food environment are particularly important.…”
Section: Introductionmentioning
confidence: 99%